Cardiomyopathy in patients after posttransplant cyclophosphamide–based hematopoietic cell transplantation. Issue 10 (6th March 2017) - Lin, Chien‐Jung; Vader, Justin M.; Slade, Michael; DiPersio, John F.; Westervelt, Peter; Romee, Rizwan
Abstract : BACKGROUND: The use of posttransplant cyclophosphamide (PT‐Cy) has contributed significantly to the success of haploidentical hematopoietic cell transplantation (HCT). Furthermore, several studies have shown promising results in the human leukocyte antigen–matched setting. However, the use of high‐dose cyclophosphamide has been associated with the development of cardiomyopathy. There is a paucity of data concerning posttransplant cardiac complications in patients undergoing PT‐Cy–based HCT. METHODS: A retrospective analysis of 176 patients undergoing HCT with PT‐Cy was performed. The overall survival, left ventricular ejection fractions, brain natriuretic peptide levels, and cardiac comorbidities were reviewed. The associations between comorbidities and the onset of heart failure were assessed with a Cox proportional hazards model. RESULTS: Pretransplant cardiomyopathy was found in 16 patients (9.1%) but had no effect on their posttransplant overall survival. Thirty‐five patients (21.9%) developed posttransplant cardiomyopathy, which correlated with increased mortality, but this was not statistically different from the frequency‐matched non–PT‐Cy cohort. The majority of these cardiomyopathies occurred in the setting of an infectious milieu. An age greater than 60 years and an HCT comorbidity index score equal to or greater than 4 were the only risk factors that correlated with posttransplant cardiomyopathy. CONCLUSIONS: The presence of pretransplant cardiomyopathy does not negatively affect overall survival for patients who undergo HCT with PT‐Cy. Furthermore, cardiomyopathy in PT‐Cy patients is not caused by PT‐Cy but is mostly concurrent with infectious complications and is associated with reduced overall survival. Traditional cardiovascular risk factors do not fully predict the occurrence of posttransplant cardiomyopathy. Future research is required to unravel predictive factors for cardiomyopathy after PT‐Cy–based HCT. Cancer 2017;123:1800–1809 . © 2017 American Cancer Society . Abstract : Mild pretransplant cardiomyopathy, found in 9.1% of transplants, does not affect overall survival. New‐onset cardiomyopathy, found in 21.9% of patients undergoing posttransplant cyclophosphamide–based hematopoietic cell transplantation, occurs in an infective milieu and is associated with decreased survival.